Effects of plant growth regulators on callus induction from Cananga odorata flower petal explant - Zain, Nurazah; Muse, Radzali; Ahmad, Syahida; Mahmood, Maziah (Academic Journals, 2009)
The Cananga odorata callus was initiated from petals of the C. odorata flowers on MS medium and B5 vitamins containing 30 g/L sugar and 3 g/L agar. The medium was also supplemented with different concentrations of 1-naphtalene acetic acid (NAA), and combinations of NAA with 6-benzylaminpurine(BAP) as the plant growth regulators. It was observed that the C. odorata callus could be induced on media containing the combination of 3 mg/L NAA and 0.5 mg/L BAP. High concentration of NAA gave rise to pale, whitish and friable callus after 1 - 2 weeks of culture. The optimum pH for the cell culture was about 5.7 and incubation at 25 ± 2°C, in totally dark condition.